2012
DOI: 10.1117/1.jbo.17.11.116020
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest assessment of cortical activation induced by repetitive transcranial magnetic stimulation with brain atlas-guided optical topography

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a technology that stimulates neurons with rapidly changing magnetic pulses with demonstrated therapeutic applications for various neuropsychiatric disorders. Functional near-infrared spectroscopy (fNIRS) is a suitable tool to assess rTMS-evoked brain responses without interference from the magnetic or electric fields generated by the TMS coil. We have previously reported a channel-wise study of combined rTMS/fNIRS on the motor and prefrontal cortices, show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 44 publications
1
34
0
Order By: Relevance
“…32 It overlays 2-D images of HbO or Hb activations/ deactivations over a standard human brain MRI atlas after 2-D angular interpolation of the channel-wise activation data in a spherical-coordinate system. The channel-wise β-values derived from GLM analysis, and t-values from subsequent statistical comparisons were used to generate activation maps (i.e., β-maps and t-maps) induced by thermal stimulation over different body sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 It overlays 2-D images of HbO or Hb activations/ deactivations over a standard human brain MRI atlas after 2-D angular interpolation of the channel-wise activation data in a spherical-coordinate system. The channel-wise β-values derived from GLM analysis, and t-values from subsequent statistical comparisons were used to generate activation maps (i.e., β-maps and t-maps) induced by thermal stimulation over different body sites.…”
Section: Discussionmentioning
confidence: 99%
“…These cranial landmarks served as reference positions to convert the realworld stereotaxic coordinates of the optodes to the Montreal Neurological Institute (MNI) coordinates used in a standard brain MRI atlas, based on the affine transformation. 32 Using NIRS-SPM software, 33 each of the Brodmann areas (BA) probed by the fNIRS optode array, and the respective percentage of covered BA over the entire area of the optode array, were identified. It was observed that the optode array mainly examined seven major Brodmann areas: BAs 6,8,9,10,44,45, and 46, all of which covered 97.42% of the area interrogated by the optode array.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Such an automated classification is critical because it helps to extract and identify cerebral hemodynamic signals from appropriately matched anatomical locations, thus improving the accuracy of interpretations of local and global brain activities. Commonly used methods for registering NIRS data on a human brain template are often based on the EEG 10-20 system, [47][48][49] which is not directly applicable to the 3-D atlas-DOT images. In addition, routinely used voxel classification in fMRI is based on an affine transformation, which converts the voxel space to MNI space, followed by a voxel matching with a standard MNI structure template.…”
Section: Development Of Automated Voxel Classificationmentioning
confidence: 99%
“…Usually both of the metrics are used to quantify the reliability of measurements. 5,8,9,11 This will provide important information on the effect of repeated testing on intertest reliability and will help make a decision on how many tests are needed. Taking the calculated ICC values in Table 7 as an example, ICCð2;1Þ ¼ 0.61 and ICCð2;2Þ ¼ 0.76 in the win case.…”
Section: Single Measurement Versus Average Of Repeated Measurementsmentioning
confidence: 99%